2000
DOI: 10.4269/ajtmh.2000.63.90
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced development in nature of larval Anopheles arabiensis mosquitoes feeding on maize pollen.

Abstract: Abstract. To determine whether pollen produced by maize (Zea m. mays) may contribute to the development of larval Anopheles gambiae complex mosquitoes, the main African vectors of malaria, we correlated duration of larval development, pupation success, and size of the resulting adults with degree of access to this potential nutriment. Maize pollen is abundant during the wet season on the surface of water near maize plantings in a malaria-endemic region of Ethiopia, and larval Anopheles arabiensis readily inges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 12 publications
1
92
1
Order By: Relevance
“…The abundance of water bodies and favorable temperatures, maize plantings, extensive deforestation, or farmland have been associated with increased larval or mosquito abundance and thus increased risk for malaria transmission in human populations. [31][32][33][34] Other studies have used geographic information systems and satellite imagery to investigate environmental factors that potentially drive the dynamics of malaria vector populations [34][35][36] and other vector-borne and zoonotic diseases such as dengue fever or hantavirus. [37][38][39] It has been shown that the efficacy of control measures such as intermittent preventive treatment (IPT) can be strongly dependent on the present malaria incidence, [40][41][42] and it can be assumed that direct and contextual effects increase with malaria risk after an intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of water bodies and favorable temperatures, maize plantings, extensive deforestation, or farmland have been associated with increased larval or mosquito abundance and thus increased risk for malaria transmission in human populations. [31][32][33][34] Other studies have used geographic information systems and satellite imagery to investigate environmental factors that potentially drive the dynamics of malaria vector populations [34][35][36] and other vector-borne and zoonotic diseases such as dengue fever or hantavirus. [37][38][39] It has been shown that the efficacy of control measures such as intermittent preventive treatment (IPT) can be strongly dependent on the present malaria incidence, [40][41][42] and it can be assumed that direct and contextual effects increase with malaria risk after an intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The invasion of malaria in the Bure highlands of Ethiopia (Kebede et al 2005) was likely mediated by an increase in the fitness of Anopheles arabiensis-the mosquito vector present in the area-that resulted from its feeding on maize pollen after this crop was introduced to the area (Ye-Ebiyo et al 2003;Ye-Ebiyo et al 2000). However, this pattern was very localized, which led to the question of why it was not a problem in other places where maize had been introduced.…”
Section: Ecological Interactionsmentioning
confidence: 99%
“…The increasing incidence of malaria in Africa has been attributed to the growing reliance on corn as a staple food crop (356). In the absence of corn pollen, the silt-laden puddles of water, in which the A. arabiensis mosquitoes breed, are very low in nutrients.…”
Section: Land Use Land Cover and Biodiversitymentioning
confidence: 99%